Underuse of statins in patients with atherosclerotic ischemic stroke in China. - Li, X; Gao, Y; Li, J; Feng, F; Liu, J; Zhang, H; Zhang, D; Hundei, W; Chen, F; Chen, Y; Chen, Z; Landray, M; et al. (2012)
BACKGROUND: Well designed randomized trials and meta-analyses have clearly shown that statins reduce the risk of major vascular events, including ischemic stroke, in a wide range of patients and their routine use is recommended for patients at an increased cardiovascular risk. Survivors of a first ischemic stroke are at a risk of recurrence and of other vascular events and statins are generally recommended to reduce this risk. This study investigated how widely statins were being used for such patients in China. METHODS: Totally 6422 patients with a history of ischemic stroke were identified by reviewing medical records at 51 highest-ranking hospitals in 14 cities in China, and invited to attend a screening clinic to assess eligibility for a randomized trial. Their current statin and other drug uses were recorded alongside clinical and demographic characteristics. Univariate chi-square test and multivariate Logistic regression were used to determine the factors associated with treatment. RESULTS: Only 24% of these patients reported currently taking a statin. The most important predictor of statin use among these patients was prior history of coronary heart disease. History of diabetes or hypertension, as well as treated in university affiliated hospitals is related to increased use. The status had improved significantly during a 2-year period. Atorvastatin (40%) and simvastatin (39%) were the most commonly used. CONCLUSIONS: In China, statins are still underused for secondary prevention among survivors of ischemic stroke. Reasons for this poor use need to be understood in order to increase use of these evidence based therapies.